Evaluation of pyrethrin aerosol insecticide as an alternative to methyl bromide for pest control in flour mills - Kharel, Kabita (Kansas State University, 2013)
Experiments were conducted to assess the effects of direct and indirect exposure scenarios, different degrees of residual flour, open and obstructed positions, and seasonal temperature variations on the efficacy of synergized pyrethrin against the red flour beetle, Tribolium castaneum (Herbst) and the confused flour beetle, Tribolium confusum Jacquelin du Val. To evaluate effects of direct and indirect exposures of T. castaneum and T. confusum eggs, larvae, pupae, or eggs to the insecticide aerosol within a flour mill, the following treatments were made to each life stage: insects treated with aerosol and transferred to treated or untreated flour, untreated insects transferred to treated flour, and insects and flour combined and treated together. Different degrees of harborage or sanitation levels were created by exposing T. confusum larvae, pupae, and adults to pyrethrin aerosol in Petri dishes containing 0, 0.1, 1, 5, and 10 g of wheat flour. Effects of pyrethrin dispersal in open and obstructed positions and seasonal temperature variations were assessed by exposing T. confusum pupae and adults in open positions and inside wooden boxes (1 m long, 20 cm wide, and 5, 10, or 20 cm high) inside experimental sheds maintained at target temperatures of 22, 27, and 32 °C. Results showed that when T. castaneum and T. confusum were directly exposed to aerosol without the flour source, or with a low amount of flour at open exposed areas, the aerosol provided good control against all life stages of T. castaneum and T. confusum. However, when insects were indirectly exposed (treated together with flour or untreated insects were transferred to treated flour), or treated together with deeper flour amounts, and exposed inside the boxes, the efficacy was greatly reduced. Eggs and pupae of both the species were more susceptible compared to larvae and adults. Additionally, the moribund adults initially observed in indirect exposure treatments, or at the deeper flour depth and exposure positions insides the boxes, were better able to recover. Generally, temperatures in the range of 22-32 °C had no significant effects on overall efficacy of pyrethrin aerosol.
Keywords: Aerosols; Synergized pyrethrin; Flour mill; Tribolium castaneum; Tribolium confusum; Temperature; Barriers; Agriculture, General (0473); Entomology (0353); Toxicology (0383)